ANALISIS DAYA TAHAN AEROBIK ATLET SELAM KABUPATEN PASURUAN PADA PEMUSATAN LATIHAN PERSIAPAN PORPROV JATIM 2019 - Aulia, Nurunnisa Sekar; Widodo, Achmad (Kesehatan Olahraga, 2021)
Maximum oxygen consumption (VO2Max) is the use or use of maximum volume of oxygen processed by the human body at the time of carrying out activities / activities that are followed or with a long duration. This maximum oxygem volume is a parameter of the body's ability expressed in liters per minute or milliliter/minute/kg of body weight. This study aims to analyze and find out the level of aerobic endurance of diving athletes Kab.Pasuruan at the concentration of preparation exercises PORPROV VI JATIM in 2019. In this study using non-experimental research type, precisely descriptive research type. In this study, the subjects used were all pasuruan diving athletes who participated in training center for the preparation of PORPROV VI JATIM in 2019. The number of research subjects was 19 people, consisting of 12 female athletes and 7 male athletes. In this study for data retrieval using Multistage Fitness Test (MFT). The results of this study can be known that for male athletes have VO2Max ability with an average value of 43.8 ml / kg / min with a good category. The result of VO2Max capability with a minimum value in male athletes is 36 ml/kg/min and the result of VO2Max capability with a maximum value in male athletes is 51.1 ml/kg/min. As for female athletes have VO2Max ability with an average score of 35.99167 ml/kg/min with good category. The result of VO2Max capability with a minimum value in female athletes is 26.4 ml/kg/min and the result of VO2Max capability with a maximum value in female athletes is 44.2 ml/kg/min. For DNI (Resting Pulse) male athletes have an average of 71 bpm, while for female athletes have an average of 76.08 bpm. The conclusion of this study mentions that the value of VO2Max or aerobic endurance of diving athletes pasuruan district in the Concentration of Preparatory Exercises PORPROV JATIM in 2019 has a good category. Keywords: diving; Aerobic endurance; VO2Max